Pumpkin carbon dot / chitosan composite membrane as well as preparation method and application thereof

By compounding pumpkin carbon dots with chitosan and adopting high-temperature carbonization method to prepare pumpkin carbon dots/chitosan composite film, the safety hazards and industrial production difficulties in the existing technology are solved, efficient and safe bio-based film production is achieved, the mechanical strength, UV blocking performance and transparency of the film are improved, and its application in preservation and smart packaging is broadened.

CN120623529APending Publication Date: 2025-09-12ZHENGZHOU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510841592.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing carbon dot preparation methods have safety risks and are difficult to meet the needs of large-scale industrial production. The mechanical strength, barrier properties and transparency of the film after the carbon dots are composited with the biological substrate are poor, and the mechanical properties and UV barrier properties of the chitosan film are insufficient.

Method used

Pumpkin carbon dots were composited with chitosan. Pumpkin carbon dots were prepared by high-temperature carbonization method and then mixed with chitosan and glycerol to form a film by casting to form a pumpkin carbon dots/chitosan composite film.

Benefits of technology

Safe and efficient large-scale production has been achieved. The pumpkin carbon dot/chitosan composite film has high toughness, low water vapor permeability, excellent UV barrier properties and good visible light transparency, broadening its application in the fields of fresh-keeping packaging and smart packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120623529A_ABST
    Figure CN120623529A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fresh-keeping materials, and particularly relates to a pumpkin carbon dot / chitosan composite film as well as a preparation method and application thereof. The preparation method of the composite membrane comprises the following steps: dissolving chitosan in an acetic acid solution to obtain a chitosan acetic acid solution; dissolving the pumpkin carbon dots in deionized water to obtain a pumpkin carbon dot aqueous solution; and blending and stirring the chitosan acetic acid solution, the pumpkin carbon dot aqueous solution and glycerol, casting in a mold, and drying to form a film. According to the method, the pumpkin flesh is used as a raw material, the raw material is wide in source and convenient to process, the pumpkin flesh is easily decomposed into a small-molecule carbon precursor in the carbonization process, in addition, the pumpkin flesh can directly form the nitrogen-doped carbon dots, no additional nitrogen source needs to be added, and the fluorescence quantum yield is increased; the problems that a single chitosan film is high in brittleness and insufficient in water resistance are solved, a degradable packaging material with ultraviolet blocking and high toughness is provided, and meanwhile good visible light transparency is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fresh-keeping materials, and in particular relates to a pumpkin carbon dot / chitosan composite film and a preparation method and application thereof. Background Art

[0002] As global environmental awareness continues to rise, the "white pollution" problem caused by traditional plastic products is becoming increasingly serious. The development of biodegradable and high-performance bio-based food materials is urgent. Chitosan is a natural, biodegradable polymer with excellent biocompatibility, film-forming properties, and broad antibacterial properties. However, single chitosan films suffer from poor mechanical properties, insufficient water resistance, and insufficient UV-blocking properties.

[0003] Carbon dots (CDs), emerging carbon nanomaterials, offer advantages such as fluorescence, antibacterial properties, high biocompatibility, and tunable surface functional groups, opening up a new path for the functionalization of bio-based membranes. CDs can be prepared through green synthesis using food processing byproducts such as peels and pomace, enabling resource recycling and aligning with environmental protection. However, the resulting bio-based membranes derived from CDs composited with bio-based materials often suffer from high processing costs for the CD raw materials, and their poor mechanical strength, barrier properties, and transparency hinder their application.

[0004] In terms of carbon dot preparation technology, existing methods include laser destruction, electrochemical etching, chemical oxidation, high-temperature pyrolysis, microwave-assisted, hydrothermal / solvothermal, ultrasonic method, template method, etc. Among them, the hydrothermal method has become the mainstream technology in the current carbon dot preparation and related composite membrane projects due to its relatively simple operation. However, this method has significant limitations: the reaction needs to be carried out in a sealed reactor, and the volume of the container directly restricts the preparation amount; there is an explosion risk in a high-pressure environment, and the safety hazards are prominent; the preparation process is complicated and it is difficult to meet the needs of large-scale industrial production. Therefore, it is urgent to develop a safe, efficient, and mass-producible carbon dot preparation and composite membrane technology solution. Summary of the Invention

[0005] In view of the shortcomings of the existing methods, the present invention provides a pumpkin carbon dot / chitosan composite film and its preparation method and application.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a pumpkin carbon dot / chitosan composite film comprises the following steps:

[0008] S1, dissolving chitosan in acetic acid solution to obtain chitosan acetic acid solution;

[0009] S2, dissolving pumpkin carbon dots in deionized water to obtain a pumpkin carbon dot aqueous solution;

[0010] S3, mixing the chitosan acetic acid solution described in step S1, the pumpkin carbon dot aqueous solution described in step S2, and glycerol, casting the mixture in a mold, and drying the mixture to form a film.

[0011] Preferably, the mass ratio of chitosan, pumpkin carbon dots and glycerol is 1:0.2%-0.8%:8%-12%.

[0012] Preferably, the ratio of chitosan to acetic acid solution is 1-1.5 g:100 mL, and the ratio of pumpkin carbon dots to deionized water is 0.002-0.012 g:100 mL.

[0013] Preferably, the volume concentration of the acetic acid solution is 0.5-1.5%.

[0014] Preferably, the method for preparing pumpkin carbon dots comprises the following steps:

[0015] The pumpkin flesh was homogenized, spread on a baking tray, baked, ground and sieved to obtain carbonized powder, which was then added to deionized water and ultrasonicated at room temperature. The powder was then filtered and the filtrate was concentrated by rotary evaporation. The concentrated solution was centrifuged to remove insoluble matter and freeze-dried to obtain pumpkin carbon dots.

[0016] Preferably, the baking temperature is 180-220° C., and the baking time is 100-140 minutes.

[0017] Preferably, the ratio of the carbonized powder to deionized water is 1 g: 8-12 mL.

[0018] A pumpkin carbon dot / chitosan composite film prepared by the above preparation method.

[0019] Application of the pumpkin carbon dot / chitosan composite film prepared by the above preparation method in the field of food packaging.

[0020] Preferably, the application includes: use in UV-blocking fresh-keeping packaging materials.

[0021] The positive beneficial effects of the present invention are:

[0022] 1. The present invention uses pumpkin flesh as a raw material for preparing carbon dots. Pumpkin is abundant in production and its cost is much lower than that of raw materials that require extraction before use. The raw material is widely available and easily accessible. Pumpkin flesh is soft in texture and can be directly used for homogenization and carbon dot preparation without complicated crushing or chemical treatment, making it more convenient to handle than hard raw materials. In addition, pumpkin flesh is rich in soluble sugars such as glucose and fructose, which are easily decomposed into small molecular carbon precursors during carbonization and more easily condensed to form stable carbon nuclei. In addition, pumpkin flesh also contains natural proteins, amino acid nitrogen, and oxygen, which can directly form nitrogen-doped carbon dots without the need for an additional nitrogen source, thereby improving the fluorescence quantum yield.

[0023] 2. The present invention adopts a high-temperature carbonization method to prepare pumpkin carbon dots (CDs). The preparation process is simple, the reaction time is short, the instrumentation is simple, and it can be produced on a large scale. Compared with the hydrothermal method, it does not need to be carried out in a sealed high-pressure reactor and is not limited by the reactor volume. It avoids the risk of explosion and improves production efficiency.

[0024] 3. Chitosan has good film-forming properties and can be used as a carrier of carbon dots to form a three-dimensional network. Pumpkin carbon dots can not only be evenly dispersed in the chitosan matrix, but also fill the gaps in the chitosan molecular chains. The surface of the pumpkin carbon dots (CDs) of the present invention is rich in hydroxyl and carboxyl hydrophilic functional groups, and the amino and hydroxyl groups on the chitosan molecular chains can form hydrogen bonds or electrostatic interactions with them. This effect enhances the compatibility and stability between the two, forming a denser composite structure. This structural synergistic effect improves the barrier properties of the material, effectively blocks oxygen and moisture, and delays the weight loss or water loss of food. The pumpkin carbon dots (CDs) of the present invention are used in combination with the chitosan matrix, supplemented with the plasticizer glycerol, and the resulting pumpkin carbon dots / chitosan composite film has an elongation at break of up to 31.30±1.35%, and a water vapor permeability of as low as 4.35±0.33 g / (m 2 ·24h), the transmittance at UVB320nm and UVA375nm in the UV blocking zone is less than 5%, and the transmittance at 550nm in the visible light zone is greater than 60%. This helps to solve the problems of high brittleness and insufficient water barrier of single chitosan film, provides a biodegradable packaging material with both UV blocking and high toughness, while maintaining good visible light transparency. It helps to broaden the application of chitosan film in the fields of fresh-keeping packaging and smart packaging (such as fluorescent sensing to monitor food freshness), and provides new ideas for the high-value utilization of biomass waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the UV-visible absorption spectrum of pumpkin carbon dots in Example 1 of the present invention;

[0026] Figure 2 This is the fluorescence spectrum of pumpkin carbon dots in Example 1 of the present invention, where: Figure 2 (A) is the excitation and emission spectra, Figure 2 (B) Emission spectra at different excitation wavelengths;

[0027] Figure 3 This is the infrared spectrum of pumpkin carbon dots in Example 1 of the present invention;

[0028] Figure 4 Mechanical properties of pumpkin carbon dot / chitosan composite films of Examples 1-4 of the present invention and chitosan film of Comparative Example 1;

[0029] Figure 5 This is a graph showing the UV blocking performance of pumpkin carbon dot / chitosan composite films of Examples 1-4 of the present invention and the chitosan film of Comparative Example 1;

[0030] Figure 6 The effects of pumpkin carbon dots / chitosan composite films of Examples 1-4 of the present invention and the chitosan film of Comparative Example 1 on the effect of thiobarbituric acid on the fish preservation process;

[0031] Figure 7 The effects of the pumpkin carbon dot / chitosan composite films of Examples 1-4 of the present invention and the chitosan film of Comparative Example 1 on the total colony count during the fish preservation process are shown. DETAILED DESCRIPTION

[0032] The present invention is further described below with reference to some specific embodiments.

[0033] Example 1

[0034] A method for preparing a pumpkin carbon dot / chitosan composite film comprises the following steps:

[0035] S1. Dissolve 1 g of chitosan in 100 mL of acetic acid solution, wherein the volume concentration of the acetic acid solution is 1%, to obtain a chitosan acetic acid solution;

[0036] S2, dissolving 0.002 g of pumpkin carbon dots in 100 mL of deionized water to obtain a pumpkin carbon dot aqueous solution;

[0037] S3. The chitosan acetic acid solution of step S1, the pumpkin carbon dot aqueous solution of step S2 and 0.1 g of glycerol were mixed and stirred for 2 h, cast into a mold, and dried at 50° C. for 3 h to obtain a CH-CDs0.2 composite film.

[0038] The method for preparing the pumpkin carbon dots comprises the following steps:

[0039] The pumpkin was peeled, pulped, and seeded. The pumpkin flesh was homogenized and spread on a baking tray. The mixture was baked at 200°C for 120 minutes and ground through a 200-mesh sieve to obtain a carbonized powder. The powder was added to deionized water and ultrasonicated at room temperature for 30 minutes. The ratio of carbonized powder to deionized water was 1 g:10 mL. The mixture was then filtered and concentrated by rotary evaporation. The concentrated solution was centrifuged at 3000 rpm for 10 minutes to remove insoluble matter and freeze-dried to obtain pumpkin carbon dots. The pumpkin carbon dots of this example were tested for performance. The results are shown in

[15] . Figure 1-3 .

[0040] The pumpkin carbon dots of the present invention were prepared into a pumpkin carbon dots aqueous solution with a concentration of 1 mg / mL, and UV-visible absorption light test was performed. Figure 1The pumpkin carbon dots exhibit good water dispersibility, emitting an orange color under natural sunlight (left) and a blue fluorescence under 365nm UV light (right). The pumpkin carbon dots exhibit a distinct UV absorption peak at 262nm, attributed to the π-π* electron transition of the aromatic C=C group and the presence of a carbon ring π orbital in the carbon dot core.

[0041] The pumpkin carbon dots of the present invention were prepared into a pumpkin carbon dots aqueous solution with a concentration of 1 mg / mL and fluorescence spectrum test was performed. Figure 2 (A) It can be seen that the red and black lines correspond to the optimal fluorescence excitation wavelength of 370nm and emission wavelength of 450nm for the carbon dots, respectively, indicating that the existence of the Stokes shift phenomenon makes the two appear mirror-symmetrical, and the emission wavelength is greater than the excitation wavelength. Figure 2 (B) It can be seen that with the increase of excitation wavelength, the fluorescence peak gradually undergoes a significant red shift, and the fluorescence intensity shows a trend of first increasing and then decreasing. This is related to the oxygen-containing functional groups and defect factors on the surface of the carbon dots, indicating that the pumpkin carbon dots prepared by the present invention have obvious excitation dependence.

[0042] Depend on Figure 3 It can be seen that in the infrared spectrum of pumpkin carbon dots, 3355cm -1 The absorption peaks at 2929cm are O—H and N—H stretching vibration peaks; -1 The absorption peak at 1729cm is the C—H stretching vibration peak; -1 、1601cm -1 、1383cm -1 、1047cm -1 The absorption peaks at are attributed to -C=O, aromatic ring C=C skeleton, C—N, and C—O stretching vibrations, respectively, indicating that the outer surface of the pumpkin carbon dots prepared by the present invention contains abundant hydroxyl and carboxyl hydrophilic groups. Therefore, the pumpkin carbon dots of the present invention have good water solubility and fluorescence stability.

[0043] Example 2

[0044] A method for preparing a pumpkin carbon dot / chitosan composite film comprises the following steps:

[0045] S1. Dissolve 1 g of chitosan in 100 mL of acetic acid solution, wherein the volume concentration of the acetic acid solution is 1%, to obtain a chitosan acetic acid solution;

[0046] S2, dissolving 0.004 g of pumpkin carbon dots in 100 mL of deionized water to obtain a pumpkin carbon dot aqueous solution;

[0047] S3. The chitosan acetic acid solution of step S1 and the pumpkin carbon dot aqueous solution of step S2 were mixed with 0.1 g of glycerol and stirred for 2 h, cast into a mold, and dried at 50° C. for 3 h to obtain a CH-CDs0.4 composite film.

[0048] The preparation method of the above pumpkin carbon dots is shown in Example 1.

[0049] Example 3

[0050] A method for preparing a pumpkin carbon dot / chitosan composite film comprises the following steps:

[0051] S1. Dissolve 1 g of chitosan in 100 mL of acetic acid solution, wherein the volume concentration of the acetic acid solution is 1%, to obtain a chitosan acetic acid solution;

[0052] S2, dissolving 0.006 g of pumpkin carbon dots in 100 mL of deionized water to obtain a pumpkin carbon dot aqueous solution;

[0053] S3. The chitosan acetic acid solution of step S1, the pumpkin carbon dot aqueous solution of step S2 and 0.1 g of glycerol were mixed and stirred for 2 h, cast into a mold, and dried at 50° C. for 3 h to obtain a CH-CDs0.6 composite film.

[0054] The preparation method of the above pumpkin carbon dots is shown in Example 1.

[0055] Example 4

[0056] A method for preparing a pumpkin carbon dot / chitosan composite film comprises the following steps:

[0057] S1. Dissolve 1 g of chitosan in 100 mL of acetic acid solution, wherein the volume concentration of the acetic acid solution is 1%, to obtain a chitosan acetic acid solution;

[0058] S2, dissolving 0.008 g of pumpkin carbon dots in 100 mL of deionized water to obtain a pumpkin carbon dot aqueous solution;

[0059] S3. The chitosan acetic acid solution of step S1, the pumpkin carbon dot aqueous solution of step S2 and 0.1 g of glycerol were mixed and stirred for 2 h, cast into a mold, and dried at 50° C. for 3 h to obtain a CH-CDs0.8 composite film.

[0060] The preparation method of the above pumpkin carbon dots is shown in Example 1.

[0061] Comparative Example 1

[0062] A method for preparing a chitosan film comprises the following steps: dissolving 1 g of chitosan in 100 mL of acetic acid solution with a volume concentration of 1%, adding 0.1 g of glycerol, blending and stirring for 2 h, casting the mixture into a mold, and drying the mixture at 50° C. for 3 h to obtain a CH film.

[0063] The composite membranes prepared in Examples 1-4 of the present invention and the chitosan membrane prepared in Comparative Example 1 were subjected to performance tests. The test results are shown in Table 1. Figure 4 and Figure 5 shown.

[0064] Table 1 Properties of the composite films of Examples 1-4 of the present invention and the chitosan film of Comparative Example 1

[0065]

[0066] As shown in Table 1, with the increase of pumpkin carbon dots addition, the pumpkin carbon dots / chitosan composite film of the present invention exhibits significant performance regulation characteristics. The elongation at break shows an upward trend, reaching a maximum of 31.30±1.35%; while the water vapor permeability shows a downward trend, reaching a minimum of 4.35±0.33 g / (m 2 ·24h); In terms of optical properties, the transmittance of the composite film in the UV-visible light region decreased significantly: when the pumpkin carbon point addition amount was 0.8%, its UV blocking performance was particularly outstanding, that is, the transmittance at the characteristic wavelengths of UVB320nm and UVA365nm was less than 5%, while the transmittance at 550nm in the visible light region was still greater than 60%. When the pumpkin carbon point content in the composite film is further increased (the pumpkin carbon points account for more than 0.8% of the chitosan mass), the tensile strength of the composite film will be lower than the minimum requirement (>10MPa) specified in the GB / T 10457-2021 standard, making it unable to withstand stress during use and tearing, significantly reducing the durability of the film. At the same time, the color of the composite film will be significantly deepened, and the transparency will be greatly reduced, affecting the visual observation of the internal packaging products. Therefore, the present invention selects pumpkin carbon dots to account for 0.2%-0.8% of the mass of chitosan. The prepared pumpkin carbon dots / chitosan composite film achieves high toughness, low water vapor permeability, excellent UV blocking and visible light transmittance, which helps to broaden the application of chitosan film in the fields of fresh-keeping packaging and smart packaging (such as fluorescent sensing to monitor food freshness), and provides new ideas for the high-value utilization of biomass waste.

[0067] Depend on Figure 4 The film obtained in Comparative Example 1 exhibited brittle properties, with tensile strength (EB) and elongation at break (EAB) of 43.50 ± 6.14 MPa and 9.02 ± 0.54%, respectively. With increasing amounts of pumpkin carbon dots, the EB value of the composite film gradually decreased, while the EAB value increased. The composite film obtained in Example 4 exhibited tensile strength (EB) and elongation at break (EAB) of 12.04 ± 0.32 MPa and 31.30 ± 1.35%, respectively. The small size and hydrophilic groups of the pumpkin carbon dots allow for uniform dispersion within the chitosan matrix. These interactions enhance the flexibility and ductility of the chitosan film through hydrogen bonding or electrostatic interactions, enabling it to withstand greater deformation without breaking. The moderate EB and EAB values ​​of the composite film are beneficial for its application in food preservation.

[0068] Depend on Figure 5It can be seen from the transmittance curve of the ultraviolet-visible spectrum that as the carbon dot content increases, the transmittance of the pumpkin carbon dot / chitosan composite film in the ultraviolet region of 200-400nm shows a downward trend, indicating that the ultraviolet absorption capacity of the composite film is positively correlated with the pumpkin carbon dot content. Due to the unique conjugated π electron structure and rich surface functional groups of the pumpkin carbon dots, a large number of active sites are provided for the ultraviolet light absorption of the composite film, enhancing the ultraviolet blocking performance of the film. In the visible light region of 400-800nm, the transmittance of the composite film of the present invention is maintained at a high level. This is attributed to the nanoscale size of the carbon dots and their excellent dispersion stability in the chitosan matrix. No obvious light scattering center agglomerates are formed, and therefore the propagation of visible light is not significantly affected, so that the composite film can maintain good transparency.

[0069] Application test

[0070] A pumpkin carbon dot / chitosan composite film is used in the field of food packaging for UV-blocking packaging materials, as detailed below:

[0071] Composite film preservation experiment process for fish meat: Prepare several fresh grass carp (3.5±0.2kg), slaughter the fish meat, remove the internal organs immediately, and transport them to the laboratory on ice. Rinse the fish meat with distilled water, cut into small pieces (2.5cm×2.5cm×1cm), wipe the surface dry with absorbent paper, and randomly divide them into 6 groups: the blank group is fish fillets without any treatment, and the experimental group is wrapped with composite films of different pumpkin carbon dot contents in Examples 1-4 of the present invention and chitosan film of Comparative Example 1, respectively. Store at a refrigerated temperature of 4°C, and evaluate the changes in thiobarbituric acid and total bacterial count in the fish meat during storage (0, 2, 4, 6, and 8 days). The test results are shown in [1]. Figure 6 and Figure 7 .

[0072] Depend on Figure 6 It can be seen that fat oxidation is a key factor affecting changes in the color and odor of fish meat, and thiobarbituric acid (TBARS) is a core indicator for measuring the freshness of fish meat and the degree of fat oxidation. The initial TBARS value of fresh fish fillets is 0.16±0.02mgMDA / kg. During the 8-day cold storage of fish meat, the TBARS values ​​of fish meat in Examples 1-4 of the present invention and Comparative Example 1 were lower than those in the blank group. In the experimental groups, as the pumpkin carbon point content increased, the TBARS value showed a regular downward trend. This result shows that all experimental groups have the ability to slow down the rate of fat oxidation. Among them, the composite membranes of Examples 1-4 of the present invention showed higher antioxidant properties than the chitosan membrane of Comparative Example 1, indicating that the composite membranes of the present invention can effectively isolate oxygen and inhibit the generation of active oxygen free radicals, thereby reducing the peroxides produced during the contact between unsaturated fatty acids and oxygen free radicals, slowing down the fat oxidation process of fish meat during cold storage, ensuring product quality, and confirming that the composite membranes of the present invention have antioxidant properties.

[0073] Depend on Figure 7 The initial total bacterial count (TVC) of fresh grass carp under refrigerated conditions was 4.15 ± 0.23 lg CFU / g. By the sixth day of refrigeration, the TVC value of the blank group exceeded the safety limit of 7 lg CFU / g for raw fish. By the eighth day of storage, the fish in Comparative Example 1 had already deteriorated, while the TVC values ​​of the CH-CDs0.2, CH-CDs0.4, CH-CDs0.6, and CH-CDs0.8 groups reached 6.89 ± 0.09, 6.75 ± 0.13, 6.33 ± 0.14, and 6.05 ± 0.12 lg CFU / g, respectively—all still below the safety limit of 7 lg CFU / g, extending the shelf life of the fish by at least 2 days. This demonstrates that the pumpkin carbon dots / chitosan composite film of the present invention can effectively inhibit microbial growth in fish, and that the pumpkin carbon dots and chitosan exhibit a synergistic antibacterial effect, significantly extending the shelf life of fish, potentially expanding its application in food preservation.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention and are not limiting. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in this field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a pumpkin carbon dot / chitosan composite film, characterized in that: The steps include: S1, dissolving chitosan in acetic acid solution to obtain chitosan acetic acid solution; S2, dissolving pumpkin carbon dots in deionized water to obtain a pumpkin carbon dot aqueous solution; S3, mixing the chitosan acetic acid solution described in step S1, the pumpkin carbon dot aqueous solution described in step S2, and glycerol, casting the mixture in a mold, and drying the mixture to form a film.

2. The method for preparing the pumpkin carbon dot / chitosan composite film according to claim 1, wherein The mass ratio of the chitosan, pumpkin carbon dots and glycerol is 1:0.2%-0.8%:8%-12%.

3. The method for preparing the pumpkin carbon dots / chitosan composite film according to claim 2, wherein: The ratio of chitosan to acetic acid solution is 1-1.5 g:100 mL, and the ratio of pumpkin carbon dots to deionized water is 0.002-0.012 g:100 mL.

4. The method for preparing the pumpkin carbon dots / chitosan composite film according to claim 3, wherein: The volume concentration of the acetic acid solution is 0.5-1.5%.

5. The method for preparing the pumpkin carbon dots / chitosan composite film according to claim 1, wherein: The preparation method of the pumpkin carbon dots comprises the following steps: The pumpkin flesh was homogenized, spread on a baking tray, baked, ground and sieved to obtain carbonized powder, which was added to deionized water and ultrasonicated at room temperature. The powder was then filtered and the filtrate was concentrated by rotary evaporation. The concentrated solution was centrifuged to remove insoluble matter and freeze-dried to obtain pumpkin carbon dots.

6. The method for preparing the pumpkin carbon dots / chitosan composite film according to claim 5, wherein: The baking temperature is 180-220° C., and the baking time is 100-140 minutes.

7. The method for preparing the pumpkin carbon dots / chitosan composite film according to claim 5, wherein: The ratio of the carbonized powder to deionized water is 1 g: 8-12 mL.

8. A pumpkin carbon dots / chitosan composite film prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the pumpkin carbon dots / chitosan composite film prepared by the preparation method according to any one of claims 1 to 7 in the field of food packaging.

10. The use according to claim 9, characterized in that The applications include: use in UV-blocking fresh-keeping packaging materials.